The impact of psychological factors on recovery from injury: a multicentre cohort study - Kellezi, Blerina; Coupland, Carol; Morriss, Richard; Beckett, Kate; Joseph, Stephen; Barnes, Jo; Christie, Nicola; Sleney, Judith; Kendrick, Denise (Springer, 2016)
Purpose Unintentional injuries have a significant long-term health impact in working age adults. Depression, anxiety and post-traumatic stress disorder are common post-injury, but their impact on self-reported recovery has not been investigated in general injury populations. This study investigated the role of psychological predictors 1 month post-injury in subsequent self-reported recovery from injury in working-aged adults. Methods A multicentre cohort study was conducted of 668 unintentionally injured adults admitted to five UK hospitals followed up at 1, 2, 4 and 12 months post-injury. Logistic regression explored relationships between psychological morbidity 1 month post-injury and self-reported recovery 12 months post-injury, adjusting for health, demographic, injury and socio-legal factors. Multiple imputations were used to impute missing values. Results A total of 668 adults participated at baseline, 77% followed up at 1 month and 63% at 12 months, of whom 383 (57%) were included in the main analysis. Multiple imputation analysis included all 668 participants. Increasing levels of depression scores and increasing levels of pain at 1 month and an increasing number of nights in hospital were associated with significantly reduced odds of recovery at 12 months, adjusting for age, sex, centre, employment and deprivation. The findings were similar in the multiple imputation analysis, except that pain had borderline statistical significance. Conclusions Depression 1 month post-injury is an important predictor of recovery, but other factors, especially pain and nights spent in hospital, also predict recovery. Identifying and managing depression and providing adequate pain control are essential in clinical care post-injury.